Conceptualising the commercial determinants of suicide: broadening the lens on suicide and self-harm prevention. (May 2023) - van Schalkwyk, May C I; Collin, Jeff; Eddleston, Michael; Petticrew, Mark; Pearson, Melissa; Schölin, Lisa; Maani, Nason; Konradsen, Flemming; Gunnell, David; Knipe, Duleeka
Summary: Suicide is preventable, yet, in many settings, robust suicide prevention strategies have not been implemented. Although a commercial determinants of health lens is increasingly being applied to industries important to the field of suicide prevention, the interplay between the vested interests of commercial actors and suicide has received little attention. There is a need to shift attention to the causes of the causes, directing more focus to the ways that commercial determinants influence suicide and shape suicide prevention strategies. Such a shift in perspective, with an evidence base and precedents to draw upon, has transformative potential for research and policy agendas dedicated to understanding and addressing upstream modifiable determinants of suicide and self-harm. We propose a framework intended to help guide efforts to conceptualise, research, and address the commercial determinants of suicide and their inequitable distribution. We hope these ideas and lines of inquiry help to catalyse connections between disciplines and open further debate and discussion as to how to take such an agenda forward.